Analysis of the #KitaSamaRasa Community #ISmile4You Campaign in Building Awareness Stop Bullying - Maulida, Bunga; Setyo Saputro, Maulana; Azzahira Alkayyisa Bahri , Zea (PT Literasi Nusantara Publisher, 2023)
This research aims to analyze the public relations campaign of #Ismile4You community which was built because they care about the issue of bullying, #ISmile4You community invites the public to be brave against negative things which every year, there must be victims who are affected by negative bullying activities. This research discusses strategy, tactics, implementation, effectiveness and evaluation of campaigns. This research approach uses a qualitative descriptive method which aims to explain clearly and in detail through interviews with two informants who have an important role in creating the campaign, and through this research can find out the events that are central and describe the #KitaSamaRasa campaign in building stop bullying awareness. will be researched. The results of this study, that the #ISmile4You community created the #KitaSamaRasa campaign to build public awareness of bullying behavior and try to embrace bullying victims so they are not traumatized. #ISmile4You himself has tried hard to break the chain of bullying. With the #KitaSamaRasa Campaign conducted by #ISmile4You it is very effective in reducing bullying perpetrators and telling them to be upstanders.